Respostas
respondido por:
2
Primeiro isolamos as letras:
x-x/6-x+x = 1/3 - 2/4 - 3/3
Calculando o MMC dos dois lados, temos:
6x/6 - x/6 - 6x/6 + 6x/6 = 4/12 - 6/12 - 12/6
Assim,
12x/6 - 7x/6 = - 18/12 + 4/12
5x/6 = -14/12
5x = -14/12 x 6
5x = -7
x = -7/5
x = -1,4
x-x/6-x+x = 1/3 - 2/4 - 3/3
Calculando o MMC dos dois lados, temos:
6x/6 - x/6 - 6x/6 + 6x/6 = 4/12 - 6/12 - 12/6
Assim,
12x/6 - 7x/6 = - 18/12 + 4/12
5x/6 = -14/12
5x = -14/12 x 6
5x = -7
x = -7/5
x = -1,4
LaisBolandin1:
Obrigado!
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás